Educational Products Quality and its Effect on Student Loyalty Through Mediating Student Satisfaction - Musa Musa; Masdar Mas’ud; Ahmad Firman; Rozita Uji Mohammed (Madrasah Tsanawiyah DDI Cilellang, 2023)
College competition, which is dominated by the state college, is very tight when it comes to improving the quality of educational products for the sake of student recruitment. Meanwhile, not many private college students promote and recommend their colleges to others. This study aims to analyze the effect of educational products on student loyalty, either directly or indirectly through the student satisfaction variable. This type of research is a survey with a quantitative approach. The research population was all students of the Makassar LP3I Polytechnic, totaling 1,246 students. The research sample consisted of 93 students, who were determined through a proportional random sampling technique using the Slovin formula. Data collection techniques using observation, questionnaires, and documentation. The collected data were then analyzed using descriptive statistical analysis, path analysis, and inferential statistical analysis techniques. The results showed that educational products had a positive and significant effect both directly on student loyalty and indirectly through student satisfaction. This research has implications for the need for study program products that meet the standards of community needs and government demands. Efforts to meet these standards will encourage tertiary colleges to provide excellent service for student satisfaction so that they remain loyal.